PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI, DISIPLIN KERJA, INSENTIF, TURNOVER TERHADAP KINERJA PEGAWAI - Putu Pande Yudiastra; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2015)
Given the importance of employee performance, the issue which is of particular interestare the factors that influence it, among others, information technology, discipline, incentiveand turnover. Otherwise in Rumah Sakit Umum Premagana Gianyar an effort to get employerswho have the performance, have noticed information technology, discipline, incentive andturnover.The formulation of the problem in this research is : whether information technologyinfluence to employees performance, whether discipline influence to employees performance,whether incentive influence on discipline, whether incentive influence on employeesperformance, whether incentive influence to turnover and turnover influence on employeesperformancein Rumah Sakit Umum Premagana Gianyar and to answer the problem, weconducted research with the study population of 130 employees at Rumah Sakit UmumPremagana Gianyar. The method used is a method of population (census) and data collectedby questionnaire. The analysis technique used is Structural Equation Model (SEM) AMOSVersion 20.Based on the results obtained conclusions include : there is significant influencebetween technology information to employee performance, there is significant influencebetween discipline to employee performance, there is significant influence between incentiveto discipline, there is significant influence between incentive to employee performance, thereis negative significant influence between the incentive to turnover and there is negativesignificant significant influence between turnover to employee performance in Rumah SakitUmum Premagana Gianyar.Keyword: information technology, discipline, incentive, turnover and performance